Etnobotani Pekarangan Masyarakat Adat Trah Bonokeling di Wilayah Kabupaten Banyumas dan Cilacap - Indah A. Sari; Sulistijorini; Y. Purwanto (The Ethnobiological Society of Indonesia, 2021)
Homegardens management, especially in rural areas of Indonesia, has yet to receive comprehensive attention, even though its benefits have been consciously felt. The Bonokeling society have traditional ecological knowledge in managing their homegardens which is interesting to study furthermore. This research aims to provide the comprehensive study about Bonokeling society on the management, roles, benefits, and prospects of homegardens development in their life. Data were collected by a qualitative and quantitative method such as measuring the area of the homegardens, observation, inventorisation, and open-ended interviews. The highest number of plant species varieties is used as food crops as many as 119. The results of this study showed that homegardens has been managed with the concept of space division. Homegardens is carried out in a simple manner, but optimizes its role as a productive ladscape that has multifunctional benefits and is not only limited used for plant cultivation. The cultivation of more varied species as food crops has been carried out as one of the adaptation strategies to support for the subsistence need and economically oriented. Homegardens development prospects can continue to be optimized in relations with the potentials, such as by innovating integrated farmed methods and cultivation more various species of plant for the purpose of diversifying material needed based on local resources.